Funcionamiento familiar y riesgo de consumo de alcohol en adolescentes, Trujillo - 2019 - Raico Hernández, Elvis Raúl (2020)
Quantitative, descriptive correlational cross-sectional research that was carried out at the Gustavo Ries de Trujillo Educational Institution, whose objective was to determine the relationship between the level of family functioning and the level of risk of alcohol consumption in adolescents. The sample consisted of 198 teenagers. Data collection is obtained through the instruments: Family cohesion and adaptability assessment scale - faces III and Questionnaire for the identification of disorders related to alcohol consumption - AUDIT test. Data were frequently selected in single and double entry tables with numerical and percentage frequencies. To determine the relationship between the variables, verify the Kendall criteria independence test, after the analysis the following conclusions were reached: 43% of adolescents have a medium level of family functioning, 40% an extreme level; 81% had a low risk of alcohol consumption. There is no significant statistical relationship between family functioning and the risk of alcohol consumption.